EOSINOFIL PASCA MENGEROK MUKOSA HIDUNG DAN PEMERIKSAAN DARAH RUTIN DI RINITIS ALERGI - Rima Yuliati Muin; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2009)
Diagnostic of rhinitis allergy was based on anamnesis, physical examinations. Examine including anterior rhinoscopy, nasal endoscope, skin test and laboratory assay of nasal cytology, eosinofil count in the blood. Eosinofil mucosal nasal brushing assay andeosinofil routine hematology can be used as other examination to diagnose rhinitis allergy and to evaluate therapy response. The aimof the study was to know the correlation between eosinofil level on mucosal nasal brushing and routine hematology in suspect allergyrhinitis. The study used cross sectional methods, and was done among 37 suspected Rhinitis Allergy patients in the Clinical PathologyLaboratory, and the Clinic of Ears, Nose and Throat at Wahidin Sudirohusodo hospital Makasar, during the period of March - August2008. Eosinofil mucosal nasal brushing assay used Hansel stain and routine hematology assay used automatic blood cell counter Sysmex1800i. The data were analyzed with Pearson Correlation test using SPSS for Windows version 12,0. In the results were found from the37 samples by a correlation test the mean eosinofil level of mucosal nasal brushing. In men was 12.9/HPF and in women was 5/HPF.While eosinofil in routine hematology in men was 1595/µl and in women was 551/µl, with p < 0.000 and r = 0.930. The conclusionso far from this study that the correlation of eosinofil count between mucosal nasal brushing and hematology routine in those patients suspect rhinitis allergy was very strong. So this test can be used as an alternative examination to diagnose rhinitis allergy.